Sieving pore design enables stable and fast alloying chemistry of silicon negative electrodes in Li-ion batteries - Jiaxing He; Youzhi Deng; Junwei Han; Tianze Xu; Jiangshan Qi; Jinghong Li; Yibo Zhang; Ziyun Zhao; Qi Li; Jing Xiao; Jun Zhang; Debin Kong; et al. (Nature Communications)
Abstract Ideal silicon negative electrodes for high-energy lithium-ion batteries are expected to feature high capacity, minimal expansion, long lifespan, and fast charging. Yet, engineered silicon materials face a fundamental paradox associated with particle deformation and charge transfer, which hinders the industrial use of advanced silicon electrode materials. Here we show a sieving-pore design for carbon supports that overcomes these mechano-kinetic limitations to enable stable, fast (de)alloying chemistries of silicon negative electrodes. Such a sieving-pore structure features an inner nanopore body with reserved voids to accommodate high-mass-content silicon deformation and an outer sub-nanopore entrance to induce both pre-desolvation and fast intrapore transport of ions during cycling. Importantly, the sieving effect yields inorganic-rich solid electrolyte interphases to mechanically confine the in-pore silicon, producing a stress-voltage coupling effect that mitigates the formation of detrimental crystalline Li15Si4. As a result, this design enables low electrode expansion (58% at the specific capacity of 1773 mAh g− 1 and areal capacity of 4 mAh cm− 2), high initial/cyclic Coulombic efficiency (93.6%/99.9%), and minimal capacity decay (0.015% per cycle). A practical pouch cell with such a sieving-pore silicon negative electrode delivers 80% capacity retention over 1700 cycles at 2 A as well as a 10-min fast charging capability.